EFFECT OF SUPPLEMENTATION OF CAFFEINE ON SPERM MOTILITY AND LIVEABILITY IN MARWARI STALLIONS - KANT, SOURABH; KUMARESAN, YASH PAL; LEGHA, R A; SHARMA, TARU; TALLURI, T R (The Indian Journal of Animal Reproduction, 2023)
Six ejaculates from each three adult stallions were collected via artificial vagina using estrus jenny as dummy.Caffeine was added to semen extender at 0.1, 0.5 and 2 mM during pre-freeze stage and cryopreserved by followingstandard protocol. The sperm kinetic parameters, membrane functionality and integrity were evaluated with computerassistedsperm analysis, a hypo-osmotic swelling test and epifluorescent microscopy, respectively. The present studyrevealed that, adding caffeine to stallion semen extender at 0.1, 0.5 and 2 mM levels had positive impact on seminalparameters compared to the control semen. Sperm kinetics (VAP, VSL and STR) and motility were increased in thecaffeine treated groups in comparison to the control group. Among these, 2mM caffeine supplemented group thepost-thaw sperm motility and other functional attributes have significantly improved compared to the other treatmentand control groups.
Keywords: Caffeine; Jack sperm; cryopreservation; kinetic parameters; acrosome integrity